Seismic loss estimation and reduction after structural rehabilitation in Chiang Rai city - Koraphon Saicheur (2018)
© 2017, Walailak University. All rights reserved. Chiang Rai is located in the North of Thailand. The city is in a seismic risk region in which many buildings have inadequate building code enforcement. This paper presents a spatial study of the seismic performance of buildings in Chiang Rai city to establish an earthquake scenario with an assumed magnitude of 5 on the Richter scale. The results of the building damage show that areas that suffer the most occur in a high density building zone. The extent of building damage in the area was about 400,000 m2in every 1 km2, or 24.79 % of the entire area. The number of human losses was calculated for 2 different times; there were about 712 deaths during the nighttime (at 2:00 AM), and 1,027 during the daytime (at 2:00 PM). Finally, the earthquake risk mitigation team was able to initiate the rehabilitation of some important existing structures to improve their seismic performance, which was carried out under moderate-seismic activity. The important buildings considered here were hospital/emergency services buildings, schools, and government offices, which resulted in the highest consequences. The reduction of the complete damage of those buildings was more than 49 %, and human losses were reduced 75 % during the nighttime and 70.85 % during the daytime. As a result, this information is a good source for government officers to use as a tool to initiate preparation plans against a repeat of this kind of disaster.